Analisis Keputusan Pembelian Perumahan Pada PT Ardan Greenland Propertindo Purworejo - Agus Fitri Yanto; Dwi Irawati (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2022)
Increasingly increasing population makes the need for housing to increase. Seeing the increasing need for housing makes business in the housing sector wide open and growing. One company engaged in housing or property is PT Ardan Greenland Propertindo Purworejo. This study aims to analyze location, service and product quality factors towards housing purchase decisions at PT Ardan Greenland Propertindo Purworejo. This study uses a method that is "descriptive" which is a research method by investigating the circumstances, conditions and situations in which the results are presented in the form of reports. The types of data used by the author are quantitative and qualitative data. Data analysis in this study uses Multiple Linear Regression with the SPSS program. The results showed that the location, service, and product quality variables were 54.7% correctly based on the test of determination, based on the t test. It can be seen that the location variables influence the housing purchase decision at PT Ardan Greenland Propertindo Purworejo, while the service does not affect housing purchasing decisions at PT Ardan Greenland Propertindo Purworejo, and product quality variables influence housing purchase decisions at PT Ardan Greenland Propertindo Purworejo. F test analysis of the influence of location, service and product quality simultaneously influence the housing purchase decision at PT Ardan Greenland Propertindo Purworejo